2021
DOI: 10.4049/jimmunol.2001047
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of Monocyte Subsets in Obstructive Sleep Apnea Syndrome Patients Leads to an Imbalanced PD-1/PD-L1 Cross-Talk with CD4/CD8 T Cells

Abstract: Obstructive sleep apnea syndrome (OSAS) represents a substantial disease of recurrent sleep fragmentation, leading to intermittent hypoxia and subsequent diseases such as cardiovascular, metabolic, or cognitive dysfunctions. In addition, OSAS is considered as low-grade systemic inflammation, which is associated with a higher incidence of cancer, severity of infections, and an overall immune dysregulation. This research project aims to comprehensively investigate the interplay of wholesome sleep and the immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…Most patients ( n = 18) revealed a moderate decrease in classical monocytes accompanied by an increase in intermediate monocytes. Seven patients showed a severe drop in classical monocytes with a strong increase in intermediate and non-classical monocytes in comparison to healthy donors [ 14 ]. The monocyte subset distribution was not correlated to the BMI or AHI of the patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most patients ( n = 18) revealed a moderate decrease in classical monocytes accompanied by an increase in intermediate monocytes. Seven patients showed a severe drop in classical monocytes with a strong increase in intermediate and non-classical monocytes in comparison to healthy donors [ 14 ]. The monocyte subset distribution was not correlated to the BMI or AHI of the patients.…”
Section: Resultsmentioning
confidence: 99%
“…Flow cytometry data revealed a significant increase in classical monocytes accompanied by a drop in intermediate and non-classical subsets in all analyzed patients ( Figure 1 ). Most of the patients even revealed monocyte distributions comparable to healthy donors in response to PAP [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nivolumab and pembrolizaumab have been brought into guidelines due to their exact efficacy (11). PD-1 and PD-L1 expression, biomarkers of inflammation, inflammatory genes, AR and EGFR signaling have clear evidence of the impact on PD-1/PD-L1 clinical outcomes (47)(48)(49)(50)(51)(52)(53)(54)(55). The reason why cemiplimab, atezolizumab, avelumab, durvalumab have not been included in the guidelines for the treatment of HCC is that their efficacy and safety is not completely certain, and several trials are still ongoing (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Markers of systemic inflammation, such as elevated neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio and α-fetoprotein are associated with poor prognosis in HCC (40). Recent evidence suggest that when cells gradually evolve into malignant tumors, PD-L1 expression increases and the interaction between PD-1 and PD-L1 inhibits the self-reactive T cells, resulting in the over balance of PD-L1, PD-L2 and PD-1 (49). It has been demonstrated that androgen (AR) receptor can inhibit PD-L1 expression in HCC cells, and AR transcriptionally represses PD-L1 by binding to its promoter.…”
Section: Influencing Factorsmentioning
confidence: 99%